2018
DOI: 10.1038/s41598-018-31378-6
|View full text |Cite
|
Sign up to set email alerts
|

The aerobic diagenesis of Mesoproterozoic organic matter

Abstract: The Xiamaling Formation in the North China Block contains a well-preserved 1400 Ma sedimentary sequence with a low degree of thermal maturity. Previous studies have confirmed the dynamic and complex nature of this evolving marine setting, including the existence of an oxygen-minimum zone, using multi-proxy approaches, including iron speciation, trace metal dynamics, and organic geochemistry. Here, we investigate the prevailing redox conditions during diagenesis via the biomarkers of rearranged hopanes from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…The ca . 1.44 Ga Hongshuizhang Formation and the 1.38 Ga Xiamaling Formation, both in northern China, are inferred to have been deposited under anoxic, but not sulphidic conditions (Luo, George, Xu, & Zhong, ; Luo, Hallmann, Xie, Ruan, & Summons, ), with the possibility of oxygenation for example in unit three of the Xiamaling Formation (Wang et al., ; Zhang et al., ). In those studies, water column chemistry was reconstructed using redox‐sensitive trace metals and biomarkers, including the absence of aryl isoprenoids, reducing the probability of photic zone euxinia (Luo et al., , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ca . 1.44 Ga Hongshuizhang Formation and the 1.38 Ga Xiamaling Formation, both in northern China, are inferred to have been deposited under anoxic, but not sulphidic conditions (Luo, George, Xu, & Zhong, ; Luo, Hallmann, Xie, Ruan, & Summons, ), with the possibility of oxygenation for example in unit three of the Xiamaling Formation (Wang et al., ; Zhang et al., ). In those studies, water column chemistry was reconstructed using redox‐sensitive trace metals and biomarkers, including the absence of aryl isoprenoids, reducing the probability of photic zone euxinia (Luo et al., , ).…”
Section: Resultsmentioning
confidence: 99%
“…Pr and Ph are in relatively higher concentration in the Hongshuizhang, Nonesuch and Xiamaling formations compared with the Velkerri Formation. Additionally, the Xiamaling contains trace concentrations of diahopanes and increased concentration of dibenzofuran interpreted to be biomarkers for aerobic diagenesis (Wang et al., ). Luo et al.…”
Section: Resultsmentioning
confidence: 99%
“…This effort builds from the principle that the surface oceans are largely in equilibrium with the atmosphere (despite some disequilibrium from oxygen production). Reports of mid‐Proterozoic basin scale ocean oxygenation exist (Planavsky, Slack, et al, ; Sperling et al, ; Wang et al, ) which, barring very low levels of primary productivity, are most easily interpreted as intervals with oxygen above 1% PAL. On the other end of traditional estimates, there is general agreement that marine anoxia was more widespread than in the modern and the oceans were likely not fully ventilated until the Phanerozoic (or at least the Neoproterozoic) (Ozaki & Tajika, ; reviewed by Lyons, Reinhard, & Planavsky, ), suggesting lower than modern atmospheric oxygen levels.…”
Section: Point–counterpoint Argumentsmentioning
confidence: 99%
“…Diagenesis under oxidising condition plays an important role in the Ts/Tm ratio, which is often low in sub-oxic environments (Moldowan et al, 1986;Peters et al, 2005), and the formation of C 30 DiaH is considered to be related to the acid-catalysis of clay minerals during the early diagenetic process (Peters et al, 2005;Baydjanova and George, 2019). The oxic environment is also considered to be favourable for the formation of C 30 DiaH (Asif et al, 2010;Jiang et al, 2018;Wang et al, 2018), and a positive correlation is often observed between the C 29 Ts and C 30 DiaH contents (Jiang et al, 2018). Additionally, thermal maturity has also been found to affect the ratios of the parameters, whereby the ratios of Ts/Tm (Chandra et al, 1994), C 29 Ts/ C 30 H, and C 30 DiaH/C 30 H (Moldowan et al, 1991;Jiang and Zhang, 2015;Fang et al, 2019) are considered to be positively correlated with thermal maturity.…”
Section: Effect Of Diagenesis On the Biomarker Distribution And Prese...mentioning
confidence: 99%